Pengaruh Penggunaan Paylater terhadap Sikap Konsumtif Mahasiswa Universitas Jambi dalam Perspektif Ekonomi Islam - Ary Dean Amri; Allif Al Fattahillah; Chealsy Amanda; Hadiah Tri Marlia Putri; Nurul Adila; Pandu Syahrez Alkautsar (Jurnal Ilmiah Universitas Batanghari Jambi, 2023)
Based on a preliminary survey conducted by researchers of 100 students of the Faculty of Economics and Business, University of Jambi using a questionnaire distributed online via Google Form, it was found that 78 students agreed that paylater affects consumptive behavior. And the results of a research study conducted by researchers also show that 97 students use Shopee PayLater with the slogan "pay later with payments in 3-6 months". This study uses a quantitative approach. The data used is primary data by distributing questionnaires to Jambi University FEB students online via the Google form. A sample of 100 people using the slovin formula was taken by random sampling method with non-probability sampling. The data analysis used was a simple linear regression analysis processed with SPSS version 29. The results of this study indicate that the variable use of the Shopee PayLater pay later payment system has a significant effect on the consumption behavior of Jambi University FEB students. From a sharia business perspective, the paylater system is actually a paylater system using a qardh contract or payment note, where no interest and only rational administration are legally permitted.